ANTIFUNGAL ACTIVITY OF Pediococcus pentosaceus ISOLATED FROM BAMBARA GROUNDNUT (Vigna subterranea (L.) Verdc.) SEEDS AGAINST Aspergillus flavus - Amidou S. OUILI; Camelia Filofteia DIGUȚĂ; Ynoussa MAIGA; Cheik Omar Tidiane COMPAORE; Aboubakar Sidiki OUATTARA; Florentina ISRAEL-ROMING; Florentina MATEI (AgroLife Scientific Journal, 2023)
In this study, 22 lactic acid bacterial (LAB) strains were isolated from Bambara groundnut seeds and assessed for their ability to suppress the development of two strains of aflatoxigenic Aspergillus flavus. The antifungal activity of LAB strains was assessed via the overlay assay. Also, HPLC methodology was used to quantify the production of lactic and acetic acid by the LAB strains with high antifungal activity. After incubation at 30°C for 72 hours, five of these LAB strains (52B1, 52C1, 74B3, 67B1, 67A9) showed high inhibitory activity against Aspergillus flavus strains. These LAB strains exhibiting antifungal potential were identified as Pediococcus pentosaceus through 16S rDNA sequencing. Furthermore, the lactic acid bacteria (LAB) strains reported lactic acid production ranging from 12.08 mg/ml to 15.38 mg/ml and acetic acid production ranging from 0.06 mg/ml to 1.68 mg/ml. Notably, antifungal experiments are conducted in a controlled setting. Further, it would be worthwhile to explore the direct application of Pediococcus pentosaceus strains or their antimicrobial agents to food products to prevent fungal growth during storage. By doing so, the use of fungicides can be avoided and lead to safer food products.
Keywords: Bambara groundnut; Pediococcus pentosaceus; antifungal activity; Aspergillus flavus